Patients’ perception of medical care in the hospital environment: the reasons of non-hospitality - Laura Marques Castelhano; Gilberto de Araujo Guimarães; Isabel Baptista (Philosophy, Ethics, and Humanities in Medicine)
Abstract Background The medical care provided by the physician is an important part of the hospital scene and the action of caring. Assessments of the physician-patient meeting are based on welcome and the physician’s ability to be perceived as hospitable by the patient. By definition, to be hospitable is to have the ability to welcome, care for, reassure, and be courteous, respectful, and trustworthy. This article aims to understand patients’ perceptions of medical care perceived as not hospitable, characterized by a lack of care and welcome, in a hospital environment, based on a complaint’s website. Method The research method used was qualitative analysis and the research strategy was documentary research. The data were collected on a complaints registration platform. The theoretical framework used was the theory of Hospitality. The study selected, coded, and categorized the complaints of 127 patients at the 09 most renowned private hospitals in Brazil. The Voyant tools assisted in the textual analysis of complaints while coding classified them into categories. Results After evaluating the reasons and elements of the complaint, the following was analyzed the encounter characterized as hostile and inhospitable and the attitudes perceived by the patients were grouped into what was defined as “the 4 D’s of non-hospitality”: dehumanization, disregard, dereliction of duty, and disability. Each of the attitudes was characterized by the physician’s behavior and the sensations, emotions, and feelings triggered in the patient. Conclusions Patients’ perception of the not hospitable encounter may be hostile or inhospitable. The physician’s attitude is an important criterion for evaluating the encounter. The physician’s attitude and the form of care are key factors in a culture focused on hospitality in the hospital environment. Hostile and inhospitable attitudes affect the physician-patient relationship and may compromise the patient’s well-being.